2003
DOI: 10.1007/s00442-003-1371-8
|View full text |Cite
|
Sign up to set email alerts
|

Floral density, pollen limitation, and reproductive success in Trillium grandiflorum

Abstract: Decreases in floral density can disrupt mutualistic interactions between plants and their pollinators, and decrease reproductive success. I addressed the relationship between floral density and plant reproductive success using two experimental approaches: a pollen supplementation experiment in 12 populations of Trillium grandiflorum that naturally varied in floral density, and a transplant experiment in which floral density was manipulated in plots at four experimental sites. In the pollen supplementation expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 35 publications
4
101
3
Order By: Relevance
“…Furthermore, pollen limitation of some species has been examined in a number of different years and by more than one researcher (e.g., there are Ͼ10 separate estimates of fruit set for Trillium grandiflorum; ref. 30), whereas other plant species have been the subject of a single study. Therefore, for each unique plant species (n ϭ 241), we calculated the weighted average magnitude of pollen limitation for the species.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, pollen limitation of some species has been examined in a number of different years and by more than one researcher (e.g., there are Ͼ10 separate estimates of fruit set for Trillium grandiflorum; ref. 30), whereas other plant species have been the subject of a single study. Therefore, for each unique plant species (n ϭ 241), we calculated the weighted average magnitude of pollen limitation for the species.…”
Section: Methodsmentioning
confidence: 99%
“…It is well documented that plant population size (especially the participation of flowering plants) and density affect the number of visits per plant and visitation rate [49][50][51][52]. First of all, flower density may affect pollen limitation [53]. Burd [54] reported that 62% of 158 plants were pollen limited at least in some places.…”
Section: Ko Ze V (Sd) Tinf (Sd) Nf (Sd) V (Sd) Tinf (Sd) Nf (Sd)mentioning
confidence: 99%
“…An adequate amount of good quality pollen to complete fertilization of available ovules is one of a variety of factors necessary for seed and fruit set [27,28,38], therefore any disorders in the male function is beginning to have repercussions on the individual reproductive success. The possible consequences of male function problems is a weakening of progeny vigor which in long-term perspective may even negatively apply to the population dynamics as has been confirmed for Ipomopsis aggregate (Pursh) V.E.…”
Section: Discussionmentioning
confidence: 99%
“…Different interdependent factors may influence pollen dispersal between individuals and among spatially separated populations, i.e. density of individuals and the activity of insect visitors are considered as most important [27][28][29][30][31][32][33]. Numerous studies have shown that plant reproductive problems are often a male-related and attributable to pollen production or quality, i.e.…”
Section: Introductionmentioning
confidence: 99%